KOMPETENSI PROFESIONAL GURU YANG BERSERTIFIKASI DAPAT MENINGKATKAN PRESTASI BELAJAR SISWA - Pristiawaty, Endang (EDUKASI KULTURA JURNAL BAHASA SASTRA DAN BUDAYA, 2015)
Essential competencies professorship is professional competence, social competence, and personal competence. Professional competency, competence in the field of substance or field of study, competence areas of learning, teaching methods, assessment systems, the value of education and guidance. Social competence, competence in the field of relationship and service, community service. Personal competence, competence value built through behaviors that teachers, has a personal and attractive appearance, impressive and teachers slang and "funky." The teacher called to be willing to learn how to teach well and fun learners and called to find a way of learning right. Let’s just say, a teacher is not only a profession that is determined through testing and certification competence alone, but involves the heart, meaning that from the beginning they had dreams of becoming a teacher, a teacher who knew him, and as a noble humanitarian duty calls followed by awards professional as well. Seritifikasi teacher is an attempt to improve the quality of teachers is accompanied by an increase in the welfare of teachers, which is expected to improve the quality of learning and the quality of education in Indonesia on an ongoing basis.